2015
DOI: 10.17945/kjbt.2015.26.3.282
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Serum Ferritin Levels in Plateletpheresis Donors

Abstract: Background: While plateletpheresis donation results in less red blood cell loss and therefore less depletion of storage iron, repeated plateletpheresis can also lead to iron depletion. To determine the safety of regular plateletpheresis donations, this study estimated donor's iron status according to age, gender, number of donations, and donation interval. Methods: The study population included 5,109 plateletpheresis donors (4,824 males, 285 females), who passed the hemoglobin (Hb) criteria for plateletpheresi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…14,15 Finally, in a study of 5000 Korean donors, 38% of male and 64% of female plateletpheresis donors had ferritin levels less than 15 ng/mL, but this study did not control for whole blood donation nor, like the other cited studies, did it perform multivariable analysis. 13 By performing multivariable regression that quantified separately RBC loss from platelet and whole blood donations, we refine the earlier studies and confirm the ability of platelet donation to sustain and potentially to create iron depletion in blood donors, even at relatively low donation frequency. This study enhances our understanding of options for mitigating iron depletion in blood donors, specifically the potential impact on product availability under ferritin testing.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…14,15 Finally, in a study of 5000 Korean donors, 38% of male and 64% of female plateletpheresis donors had ferritin levels less than 15 ng/mL, but this study did not control for whole blood donation nor, like the other cited studies, did it perform multivariable analysis. 13 By performing multivariable regression that quantified separately RBC loss from platelet and whole blood donations, we refine the earlier studies and confirm the ability of platelet donation to sustain and potentially to create iron depletion in blood donors, even at relatively low donation frequency. This study enhances our understanding of options for mitigating iron depletion in blood donors, specifically the potential impact on product availability under ferritin testing.…”
Section: Discussionsupporting
confidence: 72%
“…In the United States and Ireland, small pilot studies in male donors similarly suggested a risk for iron depletion from frequent apheresis donation . Finally, in a study of 5000 Korean donors, 38% of male and 64% of female plateletpheresis donors had ferritin levels less than 15 ng/mL, but this study did not control for whole blood donation nor, like the other cited studies, did it perform multivariable analysis . By performing multivariable regression that quantified separately RBC loss from platelet and whole blood donations, we refine the earlier studies and confirm the ability of platelet donation to sustain and potentially to create iron depletion in blood donors, even at relatively low donation frequency.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The last measure has been shown in controlled clinical trials to protect frequent blood donors from iron depletion with the result that both anemia and nonanemic consequences of iron depletion are prevented . Iron depletion has also been reported in apheresis donors, particularly platelet apheresis donors . In the face of increasing attention to this problem by community blood centers and regulatory authorities, we believe our data are important and provide evidence that no further action by SP donor centers is needed to ensure adequate iron stores.…”
Section: Discussionmentioning
confidence: 99%